Experiências com as TICs e pensamento computacional nos currículos da educação infantil - Oliveira, Erick Mateus Souza (Universidade Federal Rural do Semi-Árido, 2019)
The present work presents a research on Information and Communication Technologies considering its great insertion in the cultural practices of the children and the Computacional Thinking that can be development in games and situations of resolution of problems of the daily life. We define as objective: to investigate how the definitions of the national curricular policies related to the experiences with the ICTs and the Computational Thinking materialize in the pedagogical practices considering directions of teachers of the infantile education. We developed a qualitative and therefore interpretive research using documental research as a data construction procedure, in which we analyzed the DCNEI (BRASIL, 2009) and the BNCC (BRAZIL, 2017) and semi-structured interviews with 10 teachers of the Early Childhood Education of two public institutions , one in Angicos and one in Assu. For the analysis of the data we are inspired by some principles of Backtinian dialogism (DANTAS, 2017). We have identified that national curricular policy documents address and seek to guarantee the teaching and learning of the languages and social practices of ICTs, as well as the experiences that can promote the development of computational thinking. And, in the voices of the interviewing teachers, we defined two axes of meanings: integration of ICT in the curriculum into action and computational thinking in activities. In the analysis, we sought to identify the relationship with the recommendations of the national curricular documents and the approximations of the practices of the teachers with the development of computational thinking even when they were not aware of them. We conclude that greater investments in continuing education are necessary to discuss the analyzed documents, sometimes unknown to the teachers. However, it was possible to notice that the experiences with ICTs and Computational Thinking can be integrated into the curricula of the children's education, since they are concrete experiences of the daily life of the children.
Monografia
Keywords: Currículo; Computação; Aprendizagem da criança; DCNEI; BNCC; Curriculum; Computing; Child learning; DCNEI; BNCC; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA